A system dynamics model of the production-price behavior of the sugar industry in the Philippines - Aventino, Lindsay R.
A computer simulated model of the production-price behavior of the sugar industry of the Philippines is constructed using System Dynamics methodology. The governing dynamic equation are programmed in DYNAMO. The model, under the prevailing policies, reproduces the past history of the system (1974 to 1982) adequately. It could be used as a tool to evaluate different policies on pricing, production and marketing for long term planning. This model provides national policy makers with a scientific basis to investigate the impact of their policies with respect to the total view of the sugar industry.